Design and Development of a Web-Based DMS for Community Health Center Accreditation and Self-Assessment Using Extreme Programming - Muhammad Jonni; Hengki Nurhuda (Journal of Creative Power and Ambition (JCPA), 2026)
Accreditation document management is one of the essential components in supporting the accreditation process of Community Health Centers (Puskesmas). However, document management is still commonly performed manually using physical archives and digital files stored across multiple storage media. This condition leads to several issues, including difficulties in document retrieval, data duplication, lack of document version control, and the absence of integration between the self-assessment process and supporting accreditation documents. Consequently, monitoring activities and accreditation preparation become less effective. This study aims to design and develop a web-based Document Management System (DMS) that integrates accreditation document management with the self-assessment process in a Community Health Center (Puskesmas). The system was developed using the Extreme Programming (XP) software development methodology, which consists of the planning, design, coding, and testing phases. The application was implemented using the Laravel framework, PHP programming language, and MySQL database. System functionality was evaluated using Black Box Testing to ensure that all features operated according to user requirements. "The results show that the developed system provides integrated features for document management, document version control, self-assessment, and accreditation readiness monitoring." integrates the self-assessment process, and provides effective monitoring of accreditation readiness. Therefore, the proposed system is expected to improve the efficiency of accreditation document management and support the continuous implementation of Community Health Center accreditation.